COVID-19 potentially causes long-term deterioration of lung function: a systematic review and meta-analysis (Medical Journal of Indonesia, 2021)
BACKGROUND The COVID-19 is an emerging disease that commonly involves respiratory complaints, including acute respiratory distress syndrome. The effect of COVID-19 on pulmonary function is still unclear and only based on sporadic reports with a small sample size. This study aimed to compile evidence on the pulmonary function of patients who have recovered from COVID-19. METHODS Literature searching was conducted in PubMed, Embase, Google Scholar, Scopus, Web of Sciences, and CINAHL. Any types of studies published before June 26, 2020 and reported lung function tests of post-COVID-19 patients were included. Articles reporting data from early hospitalization were excluded. The risk of bias was measured using tools developed by the Joanna Briggs Institute. Meta-analysis was done using a meta statistical package in R and presented in the random effects model. RESULTS 378 recovered COVID-19 patients in 7 studies were included. The lung function measurement periods were varied, ranging from 14 days after hospitalization to 10 weeks after receiving rehabilitation. Meta-analyses found that the pooled mean of diffusion capacity of carbon monoxide in recovered COVID-19 patients was lower than 80% predicted, whereas the other parameters were normal. The forced vital capacity and total lung capacity showing restrictive lung disorders were significantly lower in the severe COVID-19 survivors. CONCLUSIONS COVID-19 has a negative impact on lung function for at least several weeks in the recovery period. Diffusion and restrictive problems could be the main long-term consequences of COVID-19.